2018
DOI: 10.1101/446328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Research challenges in Africa – an exploratory study on the experiences and opinions of African researchers

Abstract: Background: Insufficient research is a major impediment to growth, development and advancement of health in Africa. Africa produces less than 1% of global research output. Meanwhile, African countries face some of the toughest challenges worldwide, most of which can only be tackled through robust and efficient research. Addressing the barriers to conducting research in Africa is a step towards improving research capacity and output. This study aimed to identify the key challenges affecting research practice an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 12 publications
1
44
1
Order By: Relevance
“…The education system not being research-oriented inevitably leads to poor quality research and a low research output.The second priority area for RCS identified was the provision of research training opportunities. However, this finding stands in contrast to evidence from other studies reporting a lack of research training facilities as a key barrier to doing research in Africa[16,26].Academic institutions such as universities are usually the primary providers of research training opportunities in Africa. Meanwhile, most of these institutions lack facilities that enable the development of practical research skills and experience, such as well-equipped laboratories, computers, libraries and trained personnel[20, 24,25].The low priority factors identified in this study (providing research resources and equipment, producing research knowledge and providing funding for research), as well as the critical factors (increasing research awareness, providing research guidance, providing incentives for research and promoting research collaboration) support findings from existing literature,…”
contrasting
confidence: 87%
See 2 more Smart Citations
“…The education system not being research-oriented inevitably leads to poor quality research and a low research output.The second priority area for RCS identified was the provision of research training opportunities. However, this finding stands in contrast to evidence from other studies reporting a lack of research training facilities as a key barrier to doing research in Africa[16,26].Academic institutions such as universities are usually the primary providers of research training opportunities in Africa. Meanwhile, most of these institutions lack facilities that enable the development of practical research skills and experience, such as well-equipped laboratories, computers, libraries and trained personnel[20, 24,25].The low priority factors identified in this study (providing research resources and equipment, producing research knowledge and providing funding for research), as well as the critical factors (increasing research awareness, providing research guidance, providing incentives for research and promoting research collaboration) support findings from existing literature,…”
contrasting
confidence: 87%
“…The second step used to identify research organisations was by searching through the partners and collaborators of institutions identified in the first step. Additional organisations were identified through part of a survey previously administered by CORE Africa [16], where participants were asked to name any organisations they knew of, that provided research training in their respective countries. Our searches were then supplemented with a google search, using a variety of keywords including "research capacity", "capacity building", "research capacity strengthening", "Africa", "strengthening research capacity "improving research capacity" and "Sub-Saharan Africa".…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with this view, it is now in the hands of our West African partners and alumni hands to take over and disseminate the MooSciTIC initiative, while using it for themselves in their daily practice in the field of higher education and research. However, no true and lasting transforming effect can be achieved without the active support from governments, local policy-makers and heads of institutions [4,5]. Their willingness to provide incentives for upgrading the training of teachers and scientists and favor the development of structured, jointly coordinated national and trans-national/regional research networks is key for conquering an independent future for West Africa.…”
Section: Outcomes and Future Directionsmentioning
confidence: 99%
“…In particular, we observed that their training generally did not include proper courses on key research-oriented aspects such as literature search, article and research proposal writing, project management, scientific integrity and ethics. Such knowledge gaps have been pointed out in other studies, often by African scientists themselves [4,5]. In high-income countries, such cross-disciplinary notions are commonly provided at postgraduate levels through a combination of courses and mentoring by senior scientists during lab internships.…”
Section: Introductionmentioning
confidence: 98%